Competition among Banks and Its Psychological Effect on Employee Retention and Supply Chain Management in Indonesia - Habibullah Jimad (International Journal of Supply Chain Management, 2020)
The prime objective of this study is to examine the psychological effect of competition among banks on employee retention with the moderating effect of supply chain management. The population of the study was based on Indonesian banks. All the employee; managerial and non-managerial were selected as the respondents of the current study. Two hundred eight questionnaires were used to conduct a survey among Indonesian banks. Data were analyzed through structural Equation Modeling (SEM) by using Partial Least Square (PLS) as a statistical tool. It is found that bank competition has a significant psychological effect on employee retention through employee satisfaction and employee stress. Increase in bank competition increases the level of employee's stress and decreases employee performance. Moreover, a decrease in employee stress and bank competition has the potential to increase employee satisfaction which causes to increase employee retention. Therefore, the current study has significant implications for literature and banking industry.